Nanocristais de dióxido de titânio (TiO2) na fase rutila/anatase auxiliam na proliferação e migração in vitro de células MC3T3 - Carvalho, Loyna Nobile (2023)
Regenerative medicine is one of the most important fields of the 19th century, along with the development of nanoscale biomaterials. The combination of cells and nanomaterials can bring benefits such as tissue regeneration. Titanium dioxide is a well-studied metal with numerous applications due to its unique properties compared to other metals. In this study, titanium dioxide nanocrystals were synthesized and characterized in anatase, rutile, and brookite phases. Viability, proliferation, and migration assays were performed on MC3T3-E1 cells using TiO2 nanocrystals in different concentrations. The results show that the nanocrystals are of high purity and have different phases depending on the thermal treatment at 650 ºC and 800 ºC. The different phases and concentrations of nanocrystals did not exhibit cytotoxicity for cells and increased cell proliferation, with emphasis on RA 100, which increased cell migration compared to the control.